Factors influencing disaster response behavior of international tourists under the Tokyo Metropolitan Earthquake scenario - Choi, Sunkyung; Yoshida, Kozo; Yamaji, Hideyuki; Shindo, Hiroaki; Maharjan, Rajali (Frontiers in Sustainable Tourism, 2023)
Japan is becoming one of popular tourism destinations in the world, it is not negligible that the country is vulnerable to disasters. Although the disaster prevention policies and practices by Japanese government are implemented, there is a lack of study on understanding the disaster response behavior such as information seeking and evacuation and its affecting factors. This study clarifies factors influencing disaster response behavior of international tourists under Tokyo Metropolitan Earthquake scenarios. The questionnaire survey was conducted and the logistic regression model was used to understand affecting factors. The results revealed that the variable knowledge on disaster response behavior in earthquakes is influential for individual’s evacuation decision especially when people choose to follow others. These findings will be beneficial for tourism stakeholders and policymakers to establish effective tourism crisis management planning considering information provision, shelter allocation, and collaborative initiatives.